2016
DOI: 10.7717/peerj.1485
|View full text |Cite
|
Sign up to set email alerts
|

Lemmas induce dormancy but help the seed ofLeymus chinensisto resist drought and salinity conditions in Northeast China

Abstract: Leymus chinensis is a dominant grass in the Songnen grassland of Northern China. The lower germination caused by the presence of lemmas has proved to be an obstacle for the use of the seeds of this plant by humans. However, it is still unknown if the lemmas have other ecological roles such as resisting drought and saline conditions. Three experiments were designed to investigate the ecological roles of the lemmas in Leymus chinensis seeds. The results showed that lemmas significantly improved the amount of wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Therefore, it is possible to identify the optimum harvest time through monitoring seed physiological indexes and changes in germination during different development stages. Lin et al (2016a, 2016b) suggested that sheepgrass seed can be harvested at 39 days after peak anthesis and 10 days after the coloration of the lemmas. In our study, the results indicated that the seed water content continued to decrease during seed development and that the water content decreased significantly during 35–42 DAP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is possible to identify the optimum harvest time through monitoring seed physiological indexes and changes in germination during different development stages. Lin et al (2016a, 2016b) suggested that sheepgrass seed can be harvested at 39 days after peak anthesis and 10 days after the coloration of the lemmas. In our study, the results indicated that the seed water content continued to decrease during seed development and that the water content decreased significantly during 35–42 DAP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that the seed dormancy of sheepgrass was significantly affected by the lemma, palea, pericarp/testa, and endosperm of the seed, and their average contribution to seed dormancy was 23.4%, 6.2%, 28.4%, and 42.0%, respectively (He et al, 2016). However, the ecological and physiological role of the lemma was revealed; it plays important roles in water uptake, dehydration and salt tolerance during germination (Lin et al, 2016a). In studies, the dormancy-breaking methods for sheepgrass seed have varied from low temperature treatments to chemical agents, including PEG and GA3 (Gu, Yi & Holubowiecz, 2005; Liu, Wang & Li, 2002; Zhang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was reported that the seed dormancy of sheepgrass was significantly affected by the lemma, palea, pericarp/testa and endosperm of the seed, and their average contribution to seed dormancy was 23.4%, 6.2%, 28.4% and 42.0%, respectively (He et al 2016). However, the ecological and physiological role of the lemma was revealed; it plays important roles in water uptake, dehydration and salt tolerance during germination (Lin et al 2016a). In studies, the dormancy breaking methods for sheepgrass seed have varied from low temperature treatments to chemical agents, including PEG and GA3 (Gu et al 2005;Liu et al 2002;Zhang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Early 93 harvesting may lead to low seed vigor and poor establishment because of an insufficient level of 94 maturation, while delaying harvest can cause seed loss under unfavorable environmental 95 conditions (Leprince et al 2017). It was recently reported that the optimum harvest time for 96 sheepgrass seed is approximately 39 days after peak anthesis at which time the maximum seed 97 quality, including seed weight, and the ability to germinate have been acquired (Lin et al 2016a). 98 However, the flowering time of sheepgrass lacks uniformity, varying among cultivars and even 99 batches, which may considerably affect practical seed harvesting.…”
mentioning
confidence: 99%